2007
DOI: 10.1097/01.bpb.0000236234.64893.92
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the management of acute/unstable slipped capital femoral epiphyses in the United Kingdom and the Netherlands: results of a survey of the membership of the British Society of Children's Orthopaedic Surgery and the Werkgroep Kinder Orthopaedie

Abstract: A questionnaire was sent to all members of the British Society for Children's Orthopaedic Surgery and the Werkgroep Kinder Orthopaedie to identify points of agreement/disagreement on the management of the acute unstable slip of the upper femoral epiphysis and to compare these European results with those from a similar North American survey. Sixty-five per cent responded. Overall, both countries evaluated cases similarly and believed in their urgent management. Sixty-six per cent did not reposition the slip. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Assuming that mechanical instability of the proximal femoral physis is one of the main causes for having AVN develop [35], it would be desirable to detect those cases accurately. The current preferred treatment of acute and unstable slips is percutaneous pinning strictly in situ or with gentle closed reduction, which precludes direct inspection of the physeal stability [4,38,48,51]. Performing the capital femoral realignment procedure based on the surgical dislocation approach [21,31,52], we observed that clinically chronic or stable slips sometimes showed complete epimetaphyseal disruption at surgery and acute or unstable slips sometimes showed no epimetaphyseal disruption.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Assuming that mechanical instability of the proximal femoral physis is one of the main causes for having AVN develop [35], it would be desirable to detect those cases accurately. The current preferred treatment of acute and unstable slips is percutaneous pinning strictly in situ or with gentle closed reduction, which precludes direct inspection of the physeal stability [4,38,48,51]. Performing the capital femoral realignment procedure based on the surgical dislocation approach [21,31,52], we observed that clinically chronic or stable slips sometimes showed complete epimetaphyseal disruption at surgery and acute or unstable slips sometimes showed no epimetaphyseal disruption.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, to prevent further slip progression, surgical fixation of the epiphysis is the recommended primary treatment [2,4,16,34,38,51]. Most SCFE deformities occur with gradual displacement of the femoral head from the metaphysis and with risk of avascular necrosis (AVN) up to 4.6% [28].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons, particularly in Europe, support the role of primary osteotomy and epiphysiodesis [30][31][32][33] at the time of SCFE diagnosis. In theory, this will restore normal anatomic head-acetabular anatomy and prevent cartilage and labral damage and premature arthritis that occurs early with residual deformity.…”
Section: Femoral Osteotomiesmentioning
confidence: 99%
“…Another recent Dutch questionnaire has shown that more than half of the members of the DPOS treat children 75% or more of their time. All of these surgeons will treat DDH [4]. …”
Section: Resultsmentioning
confidence: 99%